Meeting the Needs of Special Education Students in Inclusion Classrooms - LeDoux, Cathy; Graves, Shanna L.; Burt, Winona (Journal of the American Academy of Special Education Professionals, 2012)
Based on interactions with general education teachers, observations of special education students in inclusion classrooms, and general education teachers’ input during the Response to Intervention (RTI) process, a resource teacher found that many teachers were ill prepared to meet the diverse needs of special education students in the inclusion classroom. More importantly, the students’ Individualized Education Plans (IEPs) were not being implemented. As such, an action research project was initiated to explore three main research questions: (1) What challenges do special education students present for general education teachers in inclusive classrooms?; (2) What are the perceived needs of general education teachers in relation to accommodating special education students in their classrooms?; and (3) In what ways can administration support general education teachers in accommodating special education students? The findings identify general education teachers’ need for better communication, professional development concerning children with disabilities, and a need for more planning time.